2020
DOI: 10.1108/ijlma-01-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Addressing age stereotyping against older workers in employment

Abstract: Purpose The purpose of this paper is to report on an analysis of direct age discrimination cases by the Court of Justice of the European Union (CJEU) and the UK courts and employment tribunals over an 11-year period. The paper focusses upon age stereotyping towards older workers and analyses whether it is endorsed at the European level and/or national level. Design/methodology/approach This research has analysed a sample of 100 employment tribunal judgments concerning direct age discrimination together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Wood et al (2008) concluded that even though age discrimination is prevalent, its causes and resolution are contentious. Bengtsson (2020) found that there is significant stereotyping concerning age discrimination. This subtlety makes it challenging to remedy.…”
Section: Labor Force Complexitiesmentioning
confidence: 99%
“…Wood et al (2008) concluded that even though age discrimination is prevalent, its causes and resolution are contentious. Bengtsson (2020) found that there is significant stereotyping concerning age discrimination. This subtlety makes it challenging to remedy.…”
Section: Labor Force Complexitiesmentioning
confidence: 99%
“…While the government has legislated to protect against age discrimination (Section 12), ageist practices nevertheless continue to be a threat to achieving EWLs (Age UK, 2017;Bengtsson, 2020;European Commission, 2015;Van der Horst, 2019), leading to negative employment practices affecting older workers (Loretto et al, 2000;Taylor and Walker, 1998). Research conducted by Censuswide on behalf of Aviva (Aviva, 2018) found that while nearly two thirds of employed people over 50 are planning to retire later than they thought they would a decade ago, 44% felt their employer did not support their career ambitions.…”
Section: Agementioning
confidence: 99%
“…Even compulsory measures are not being implemented as intended and legislation to protect against age discrimination has failed to prevent ageist practices and discrimination in age management policies, training, promotion and recruitment, which many perceive as a significant barrier to achieving EWLs, especially for women (Age UK, 2017;Bengtsson, 2020;European Commission, 2015;Van der Horst, 2019). Research finds that many employers (of all sizes) are unsure about the requirements related to age discrimination and flexible working policies.…”
Section: Main Conclusionmentioning
confidence: 99%